ESRA19-0050 A subfascial local anesthetic injection to the psoas major muscle combined with the anterior approach for quadratus lumborum block: technical description and retrospective evaluation. (30th August 2019) - Yoshida, T; Nakamoto, T; Kamibayashi, T
Abstract : Background and aims: The anterior approach for quadratus lumborum block seldom involves the genitofemoral nerve. The genitofemoral nerve lies within the psoas major muscle (PMM) and arrives anterior to it, piercing its fascia. Therefore, we injected a local anesthetic in the subfascial layer of the PMM in order to block the genitofemoral nerve. Herein, we have described the technique of subfascial injection to the PMM and the anterior quadratus lumborum block, and retrospectively evaluated the distribution of sensory blockade. Methods: A curvilinear ultrasound transducer was placed immediately above the anterior superior iliac spine on the mid-axillary line in patients lying supine to obtain a 'shamrock view.' With this ultrasound image, a needle was inserted adjacent to the anterior side of the transducer and advanced in a medial direction in plane with the transducer, toward the plane between the quadratus lumborum muscle and the PMM, to inject 20 mL of levobupivacaine (0.25%). Next, the needle was further advanced until its tip penetrated the PMM fascia; another 10 mL levobupivacaine was then administered. To assess a sensory block spread of this technique, we reviewed the medical records of patients who underwent it between July and December 2018 in our hospital. The IRB approved this evaluation. Results: Seven patients undergoing endovascular aneurysm repair received 11 blocks in total. The genitofemoral nerve was blocked in nine of them, whereas the iliohypogastric, ilioinguinal, and lateral femoral cutaneous nerves were blocked in all the procedures. Conclusions: The subfascial local anesthetic injection to the PMM is promising to obtain the genitofemoral nerve block.